PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE JIGSAW UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Mega Mukti (DIADIK, 2022)
This study aims to describe the application of the Jigsaw type cooperative learning model that can increase the creativity of eighth grade students of SMP Muhammadiyah Pagar Alam, to describe the application of the Jigsaw type of cooperative learning model to improve the learning achievement of eighth grade students of SMP Muhammadiyah Pagar Alam, and to describe the effectiveness of the application of the cooperative learning model. Jigsaw type as an effort to improve student achievement in class VIII SMP Muhammadiyah Pagar Alam. This research is a Classroom Action Research (CAR) which was carried out in three cycles, followed by a quasi-experimental study. Each cycle consists of four stages, namely action planning, action implementation, observation and reflection. The subjects of this study were students of class VIII SMP Muhammadiyah Pagar Alam in the academic year 2021/2022. Data collection techniques through observation and tests. Data analysis techniques using the average formula and t-test. From the results of the study, it can be concluded that the application of the jigsaw type of learning model can increase creativity and student achievement and effectively improve the learning achievement of class VIII students at SMP Muhammadiyah Pagar Alam